1997
DOI: 10.1086/514025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peru‐15, a New Live Oral Vaccine for Cholera, in Volunteers

Abstract: A new live oral cholera vaccine, Peru-15, was studied for safety, immunogenicity, and excretion in 2 groups of healthy volunteers. Twelve inpatient volunteers received freshly harvested vaccine in doses of either 10(7) or 10(9) cfu. Subsequently 50 outpatient volunteers received freeze-dried vaccine in doses of 10(8) or 10(9) cfu or placebo in a three-cell, double-masked, placebo-controlled trial. The strain was well tolerated at all dose levels, and it stimulated high levels of vibriocidal antibodies in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 16 publications
4
24
2
Order By: Relevance
“…These observations are consistent with the immunogenicity profiles and the lack of significant side effects in previous studies involving 85 subjects who ingested various doses of Peru-15 (7,12,13). In a controlled study (7), freshly harvested Peru-15 (2 ϫ 10 8 CFU) was administered to 11 volunteers.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These observations are consistent with the immunogenicity profiles and the lack of significant side effects in previous studies involving 85 subjects who ingested various doses of Peru-15 (7,12,13). In a controlled study (7), freshly harvested Peru-15 (2 ϫ 10 8 CFU) was administered to 11 volunteers.…”
Section: Discussionsupporting
confidence: 91%
“…In another set of studies (12), two groups of six inpatient volunteers received freshly harvested vaccine in doses of either 10 7 or 10 9 CFU. Loose stools were the most common side effect, but only one volunteer met the definition of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parent strain Peru-15 has been found to be safe and immunogenic in Ͼ400 subjects, including North American adults (11,(14)(15)(16) and Bangladeshi adults (12) and children (13). We demonstrated that a single oral dose of Peru-15 pCTB was without significant reactogenicity or toxicity at dosages up to 10 10 CFU.…”
Section: Discussionmentioning
confidence: 85%